47.1k views
0 votes
What’s the answer?
^^^^^^^^^^^^^^
(PLEASE ANSWER NOW)

What’s the answer? ^^^^^^^^^^^^^^ (PLEASE ANSWER NOW)-example-1

1 Answer

6 votes

Hey there!

Solving for equation: y = 9x + 2

Replace (for now) 9x + 2 for y in the equation: y = 3x + 12

y = 3x + 12

↪ 9x + 2 = 3x + 12

ADD by -3 on both of your sides

9x + 2 + (-3x) = 3x + 12 + (-3x)

If you solved that correctly you should get: 6x + 2 = 12

ADD by -2 on both of your sides

6x + 2 + (-2) = 12 + (-2)

Cancel out: 2 + (-2) because it gives you 0

Keep: 12 + (-2) because it helps us solve for our x-interpret

12 + (-2) = 10

NEW EQUATION: 6x = 10

DIVIDE by 6 on your sides

6x/6 = 10/6

Cancel out: 6x/6 because it gives you 1

Keep: 10/6 because it helps us solve for our x-intercept

10/6 = 10÷2/6÷2 = 5/3

Thus our x = 5/3

Solving for y = 9x + 2

Replace x with 5/3 since we found our x

y = 9(5/3) + 2

9(5/3) = 15

15 + 2 = 17

Thus our y = 17

Overall answer: a = 5/3 & y = 17 ✅ (Option D)

Good luck on your assignment and enjoy your day!

~LoveYourselfFirst:)

User Darren Shewry
by
5.6k points